If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 3x + 9 = -3 Reorder the terms: -7 + 9 + 3x = -3 Combine like terms: -7 + 9 = 2 2 + 3x = -3 Solving 2 + 3x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -3 + -2 3x = -3 + -2 Combine like terms: -3 + -2 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667
| m^4+m^2n^2+n^4=0 | | 7(8/5) | | a^2-b^2-10a+25= | | 8/5(7) | | 4x-3x-10=-2 | | (x^3)+6(x^2)+11x+6=0 | | x+2+x+x=6-3 | | F(x)=4x-9-x^3 | | 7k+6=69 | | 4-7(3x-1)=-4x+28 | | 127=(16*59.3/x)(16*9.9/x) | | p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 | | 10xwhat=990 | | 4x+6=4+3x | | 5t-9=31 | | 7k-5=30 | | 6a-5=43 | | -30-6a=2(1-7a) | | 7a^2-24a-4=0 | | 31+6n=-5(1-3n) | | 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n |